Vapor-Liquid-Liquid Equilibrium (VLLE) Data for the Systems Ethyl acetate + Water, Toluene + Water and Toluene + Ethyl acetate + Water at 101.3 kPa. Using Modified Equilibrium Still - A. Mohammed, Ghazwan; O. Abdullah, Mahmoud; B. Kashmoula, Talib (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
Isobaric Vapor-Liquid-Liquid equilibrium data for the binary systems ethyl acetate + water, toluene + water and the ternary system toluene + ethyl acetate + water were determined by a modified equilibrium still, the still consisted of a boiling and a condensation sections supplied with mixers that helped to correct the composition of the recycled condensed liquid and the boiling temperature readings in the condensation and boiling sections respectively. The VLLE data where predicted and correlated using the Peng-Robinson Equation of State in the vapor phase and one of the activity coefficient models Wilson, NRTL, UNIQUAC and the UNIFAC in the liquid phase and also were correlated using the Peng-Robinson Equation of State in both the vapor and liquid phases.